Home front - Hannah, Kristin (St. Martin's Press, 2012)
"From a distance, Michael and Joleen Zarkades seem to have it all: a solid marriage, two exciting careers, and children they adore. But after twelve years together, the couple has lost their way; they are unhappy and edging toward divorce. Then the Iraq war starts. An unexpected deployment will tear their already fragile family apart, sending one of them deep into harm's way and leaving the other at home, waiting for news. When the worst happens, each must face their darkest fear and fight for the future of their family. An intimate look at the inner landscape of a disintegrating marriage and a dramatic exploration of the price of war on a single American family, HOME FRONT is a provocative and timely portrait of hope, honor, loss, forgiveness, and the elusive nature of love"--